STUDIES PROFITABILITY OF RESTAURANTS - Cristiana Tindeche (Annals of the University of Craiova: Economic Sciences Series, 2015)
Fast foods are internationally expanding at an amazing pace. Because fast-food products are delicious, abundant, relatively cheap and available in any moment of the day, this type of restaurants are found almost everywhere, and in addition, these have home delivery options, are appreciated and consumed by all age categories, so that fast-food has become a worldwide appreciated phenomenon. In support of the previous mentions, we shall emphasize an economic analysis performed for the Burger King Plaza Restaurant during 2010-2011. The results of the analysis may be appreciated as for being satisfying, although there is a need for improvement if this unit is to cope to the current and future conditions.